COMPOSIÇÃO QUÍMICA OBTIDA POR CG-EM DA FRAÇÃO ORGÂNICA DO BIO-ÓLEO PRODUZIDO EMPREGANDO RESÍDUOS DE INHAME - SOUZA, R. S.; PIVA, R. C.; LAZARRI, E.; CARAMÃO, E. B.; CARDOSO, C. A. L. (ANAIS DO ENIC, 2016)
-